Desentralisasi, Sistem Pengendalian Akuntansi Dan Kinerja Organisasi - Ietje Nazaruddin; Erni Suryandari; Barbara Gunawan (Universitas Muhammadiyah Yogyakarta, Indonesia, 2003)
This study examines the relationship between the use accounting controls system and decentralization with manager’s performance on public sector organizations. Decentralization refers to the level autonomy delegated to the manager’s public sector organizations. Responses of 45 managers public sector organizations in Yogyakarta were analyzed by using a path analytic technique. The relationships between variables were specified by a series of path coefficient, which are equivalent to standardized beta coefficient. The result studies indicate a positive and significant relationship between decentralization and use of accounting controls system, thereby supporting H1. Other result reveal a positive and significant relationship between the use of accounting controls system and decentralization with performance, thus H2, H3 could be supported. The results of study indicate that the use of accounting controls system acts as mediator in the relationship between decentralization of decision making and performance of managers public sector on Yogyakarta. The result reveal that increased level of decentralization is associated with and increased use accounting controls system which, in turn, is associated with improved managers performance on public sector organizations